The performance of lightweight concrete containing treated oil palm shell aggregate under different curing condition / Nurhasyimah Ahmad Zamri - Zamri, Nurhasyimah Ahmad (2023)
Concrete made from oil palm shells, also referred to as OPS concrete has a great deal of potential for use in the construction industry. Despite having a lot of potential to be developed as one of the built structures, this material is not presently used commercially in the construction industry because of its unusual physical condition and properties compared to other aggregates. Therefore, it is important to treat this material before using it in concrete as well as to explore and understand the behaviour of OPS-treated concrete over a long period of time in order to gain more reliable conclusions about the use of OPS in built structures. This study discusses in detail the experimental study of the overall performance of lightweight concrete made of OPS treated by a synthetic polymer which is styrene acrylic emulsion (SAE). The SAE coats the OPS surface at different volume percentages as an overall replacement for natural coarse aggregate at different curing conditions. In order to increase the performance of OPS treated concrete, testing under various curing conditions is essential to determine the best performance for OPS treated concrete.